Implementasi Algoritme Kriptografi SIMON pada Arsitektur Amazon Web Services - Sastra Ginata; Ari Kusyanti; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Amazon Web Services (AWS) is one of the cloud computing services which has been primarily used by most of the big industries recently. One of the AWS services which has the advantage to store online data is the Amazon Simple Storage Service (Amazon S3). In this particular service features, there is a data security options, specifically Amazon Client Side Encryption, that works by securing the object and using the key that has been stored by the user in the hand of the client which later would be uploaded to the bucket of the Amazon S3. One of the vital state organization in the United States, National Security Agency (NSA), has launched a cryptography algorithm named SIMON. SIMON Algorithm is a block cipher algorithm that could be applied either in the software or hardware depending to the needs of the users themselves. SIMON Algorithm is applied in the website system by using Python, that is used for encrypting the file which later would be uploaded to the chosen bucket. Based on the result of time performance test, the average speed of both encryption and decryption files are 33.7 seconds and 28.5 seconds. And in the variaton file testing, the result showed that the SIMON algorythm is capable of encrypting files with the extention file: .txt, .docx, .pdf, .png, .jpg, .mp3, .m4a, .mp4 dan .mkv.